Analisis Perhitungan Pajak Kendaraan Bermotor Dan Bea Balik Nama Di Pusat Pengelolaan Pendapatan Daerah Wilayah Kabupaten Cirebon I Sumber - Deny Pratama; Rusto Nawawi; Yeyen Parlina (PT. Berkah Digital Teknologi, 2025)
One source of income that makes a major contribution to Cirebon Regency is motor vehicle tax and transfer fees because many people use motorized vehicles, both two-wheeled and more. However, not all people comply with the tax burden that must be paid, among the causes is the absence of an image or estimate of how much the tax burden must be paid each tax due. This study aims to find out how to calculate motor vehicle tax and motor vehicle transfer fees at the Regional Revenue Management Headquarters for Cirebon I Sumber Regency. As for the realization of Motor Vehicle Tax revenue in 2020 with an ineffective assessment it only reached 73.22%, in 2021 with a very effective assessment it reached 104.04%, in 2022 with a very effective assessment it reached 103.24% and Motor Vehicle Name Transfer Fee receipts in in 2020 with an ineffective rating of only 75.89%, in 2021 with a very effective rating of 104.84%, in 2022 a very effective assessment of 101.36%. The analytical method used is descriptive qualitative analysis which is trying to describe a social phenomenon that is focused on solving problems in the present and the future. The results of the study show that the motor vehicle tax calculation system and motor vehicle transfer fees in P3DW Cirebon Regency are in accordance with West Java government regulations. It is better to evaluate the education or introduction to the public regarding how to calculate PKB and BBNKB so that it becomes easier, simpler, informative and innovative.